Suspended particulate matter and its management system surrounding opencast coal mines - Yadav A.K.; Jamal A. (My University, 2025)
The development of effective strategies for the management and control of air pollution is a key environmental challenge that society faces today. The most visible impact of mining on the environment is on air quality. Mining activities continuously degrade the quality of air by contributing suspended particulate matter (SPM). The impact of mining on the environment and on the quality of air, in particular, influences not only the health of mining professionals, but the health of nearby populations. Furthermore, suspended solids in the form of particulate matter affect mining production and the condition of the mining machinery. SPM management in surface or opencast mines is an issue that must be monitored and controlled at every mine. The present study examines SPM pollution in mines and in areas surrounding various mining operations. It also discusses the management of particulate matter. © 2018 Wiley Periodicals, Inc.